DETECTION OF Vibrio choleraeO1 SEROTYPE IN ICE PRESERVATIVES OF SEA PRODUCTS AT KEDONGANAN FISH MARKET, KUTA, BALI - Wijaya P, IGM; A, P Yuniadi; WS, IP Ananta; Dhinarananta, IGP; Hendrayana, M Agus (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana)
Vibrio cholerae is one of gut attacking bacteria in which 20% of the victims suffered acute diarrhea and 10-20% of them were severe, in addition the mode of case in Indonesia are increasing. Bali is a threatened area especially by ice preservative of sea products investement since it has a tropical climate with tons of sea products, and one of most popular fish market is Kedonganan Fish Market. We were conducting a descriptive observational with explorative study which is aimed to detect V. cholerae investation in ice preservative. The samples are ice or melted ice which are used to preserve sea product at Kedonganan Fish Market and each were choosed randomly. The samples processed in Alkaline Peptone Water (APW) and planted on TCBS media for microbiological culture exploration which refer to Kobe University protocol of V. cholerae isolation from environment; painted for gram evaluation based on our departement’s procedures; and latex serology evaluation using tools of V. cholerae O1 AD ‘seiken’. Of 10 samples obtained, 21 single bacterial colonies were found, in which 8 of them were suspected as V. cholerae’s colonies based on microbiological culture and gram painting evaluation. The suspected colonies are then undergone latex serology test to make sure the existence of V. cholerae and knowing its serotype. Based on the result analysis and interpretation of microbiological culture test, gram painting, and serology exploration, its found that 50% of samples were invested by Inaba type of V. cholerae O1. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Vibrio cholera, inaba, ice, Kedonganan Fish Market